Brefeldin A–sensitive ER‐Golgi vesicle trafficking contributes to NLRP3‐dependent caspase‐1 activation. Issue 3 (28th December 2018) - Hong, Sujeong; Hwang, Inhwa; Gim, Eunji; Yang, Jungmin; Park, Sangjun; Yoon, Sung-Hyun; Lee, Won-Woo; Yu, Je-Wook
ABSTRACT: Endoplasmic reticulum (ER)‐Golgi vesicle trafficking plays a pivotal role in the conventional secretory pathway of many cytokines; however, the precise release mechanism of a major inflammasome mediator, IL‐1β, is not thought to follow the conventional ER‐Golgi route and remains elusive. Here, we found that perturbation of ER‐Golgi trafficking by brefeldin A (BFA) treatment attenuated nucleotide‐binding oligomerization domain‐like receptor family, pyrin–domain–containing 3 (NLRP3) inflammasome activation in mouse bone marrow–derived macrophages (BMDMs). BFA treatment inhibited NLRP3‐mediated inflammasome assembly and caspase‐1 activation but did not block IL‐1β secretion from BMDMs following BFA administration after NLRP3 inflammasome activation. Consistently, short‐hairpin RNA–dependent knockdown of BFA‐inhibited guanine nucleotide‐exchange protein 1 (BIG1), a molecular target of BFA and an initiator of Golgi‐specific vesicle trafficking, abolished NLRP3‐dependent apoptosis‐associated speck‐like protein containing a caspase‐recruitment domain oligomerization and caspase‐1 activation in BMDMs. Similarly, knockdown of Golgi‐specific BFA‐resistance guanine nucleotide exchange factor 1, another target of BFA, clearly attenuated NLRP3‐mediated caspase‐1 activation in BMDMs. Mechanistically, inhibition of BIGl‐mediated vesicle trafficking did not impair NLRP3‐activating signal 2‐promoted events, such as potassium efflux and mitochondrial rearrangement, but caused significant impairment of signal 1‐triggered priming steps, including NF‐κB–mediated pathways. These data suggest that BFA‐targeted vesicle trafficking at the Golgi contributes to activation of the NLRP3 inflammasome signaling.—Hong, S., Hwang, I., Gim, E., Yang, J., Park, S., Yoon, S.‐H., Lee, W.‐W., Yu, J.‐W. Brefeldin A–sensitive ER‐Golgi vesicle trafficking contributes to NLRP3‐dependent caspase‐1 activation. FASEB J. 33, 4547–4558 (2019). www.fasebj.org